The Theological Concept of QS. Al’Ashr in People Empowerement: Muhammadiyah Perspective - Tentiasih, Septyana; Romlah; Abdul Razak, Khadijah (AT-TAJDID: Journal of Islamic Education, 2025)
Muhammadiyah, an Islamic movement that is still active and continues to develop as a social community organization, has shown a strong commitment to people empowerment. In its efforts to improve the quality of life of the ummah and encourage socio-economic progress, Muhammadiyah has established thousands of charities, including educational institutions from primary to tertiary levels, as well as health institutions such as clinics and hospitals. In addition, Muhammadiyah has hundreds of social institutions, such as orphanages and nursing homes. The movement was founded in 1912 by Kiai Ahmad Dahlan in Yogyakarta as a solution to the various problems faced by Muslims in Indonesia at that time. The research method used in this study is to use a qualitative approach with the type of library research. The purpose of this research is to find out about the theological concept of QS Al-Ashr in empowering people in Muhammadiyah's perspective. The result of this research is Muhammadiyah's approach to people empowerment is based on the concept of Al'Ashr theology, especially in time management and productive actions. Surah Al'Ashr from the Qur'an becomes an important foundation in the effort to empower people, by emphasizing the importance of faith, good deeds, and advising each other for truth and patience. Muhammadiyah has implemented this concept in various activities, including education, health, and social services, with a focus on the welfare of the community.